Assessing the Integration of Health Management Policies and National Health Security Strategies in Saudi Arabia - Alharthi, Hani Fadel; Alelyani, Awdah Mishaal; Althobity, Khalid Mohammed; Alnefaie, Bandar Mohammed Matrouk; Alsharif, Tirad Hassan; Alzahrani, Saif Abdullah Saleh; Althobaiti, Fahad Awwadh Mohammed; Alharthi, Abdullah Awwad; Al-Thobaiti, Sultan Mohammed; Sulimany, Reem Adnan Aied (Journal of Posthumanism, 2024)
Background: The integration of health management policies with national health security strategies has become a critical priority in the wake of emerging infectious diseases and global health emergencies. For Saudi Arabia, the dual imperatives of Vision 2030 reforms and preparedness for crises such as COVID-19 and MERS create a unique context in which alignment must be systematically evaluated. Aim: This study investigates the extent of integration between health sector management reforms and national health security frameworks, identifying strengths, gaps, and policy implications. Methods: A mixed-methods design was employed, combining document analysis of 27 national and international policy sources with survey data from 186 policymakers, administrators, and healthcare professionals. Semi-structured interviews with 20 key informants further contextualized findings. Data were analyzed using thematic coding in NVivo and quantitative modeling in SPSS and SmartPLS. Results: Convergence was observed in preventive healthcare priorities, mass gathering preparedness, and digital health investments. However, divergences emerged in resource allocation, data governance, and the sustainability of coordination mechanisms. Survey scores revealed strong perceptions of preparedness (M = 70.8/100) but weaker ratings of inter-agency coordination (M = 64.3/100). Comparative analysis showed Saudi Arabia excels in mass gatherings health security but lags behind international peers in institutionalizing long-term integration. Conclusion: While Saudi Arabia has advanced considerably in aligning reforms with security goals, the system requires durable governance frameworks, interoperable data structures, and routine intersectoral collaboration. Institutionalizing these elements under Vision 2030 will ensure that short-term crisis agility translates into sustained national resilience.